Change in obesity‐related metabolic abnormalities associated with body mass index improvement through life‐style intervention: A meta‐regression. Issue 2 (27th December 2019) - Matson, Rhys IB; Perry, Rachel; Hunt, Linda P; Chong, Amanda HW; Beynon, Rhona; Hamilton‐Shield, Julian; Birch, Laura
Abstract: The reduction in body mass index standard deviation score (BMI‐SDS) associated with improvement in biomarkers relating to metabolic health in obese children is unknown. We aimed to establish the change in BMI‐SDS associated with improved inflammation, liver function, and insulin resistance to inform clinical guidelines for pediatric weight management interventions and to assess the efficacy of future trials. A large‐scale systematic review was conducted to identify relevant studies. Studies of children with a diagnosis of obesity according to defined BMI thresholds, participating in lifestyle interventions to reduce obesity, were included. Studies must have reported baseline (pre‐) and postintervention (or change of) BMI‐SDS and either fasting glucose, homeostatic model of insulin resistance (HOMA‐IR), alanine aminotransferase (ALT), C‐reactive protein (CRP), or interleukin‐6 (IL‐6). A series of meta‐regressions were conducted to establish links between BMI‐SDS change scores and change in metabolic markers of health. Sixty‐eight articles were identified. From the meta‐regression analyses, across all study subsets, greater mean falls in all four parameters, (HOMA‐IR, Glucose, ALT, and CRP) were observed with greater mean loss of BMI‐SDS, but the trends were only statistically significant for HOMA‐IR and CRP ( P = .003; P = .021). However, we could not find minimum changes in BMI‐SDS that would ensure a fall in these outcomes. At this time, we are unable to recommend a definitive value of BMI‐SDS reduction needed to improve the markers of metabolic health. Future trials should aim to report additional indices of derived BMI values, which may better reflect changes in actual adiposity.